Educational Reforms in the Context of Contemporary Civilizational Changes - Zhukova, Marina Alexandrovna (2021)
Analysis of educational system seems to be the most reasonable when the key points are reformation and modernization of education, since the mentioned processes are the response to transformations in adjacent social spheres caused in their turn by objective changes, which may include civilizational, transnational changes in education at national level. This article is devoted to the estimation of educational reforms in the context of contemporary civilizational changes. The research aimed to systematize the features of development of reforms in the field of education, to develop measures on coordination of activities among main participants in educational process, to determine its main features in the context of civilizational changes. It has been established that the key point is to detect balance between autonomous right of a university to render education and scientific studies for economy and society, and responsibility of state for assurance of quality, accountability, integrity, and availability of education. It has been proved that the education sector needs investment to improve learning and research conditions. Another issue is implementation of new forms of financing, including on competitive basis, to support interest and interaction between universities and business environment. It has been determined that new trends in cooperation should not only concern the development of innovations and commercialization but also attract employers to cooperation aiming at development of new or updating the existing learning programs.